Arab Sunni-WahhÃ¢bism and Shia Iran: From Sectarian Conflict, to the Domination of the Gulf Region - Zaenuri, Ahmad; Irfan, Ahmad (Al-Bayyinah, 2023)
Discussions regarding the conflict between Saudi Arabia and Iran in the Middle East have always been framed as a sectarian conflict between Sunni-WahhÄbism and Shia. The study data presented in this article provide a distinct, exhaustive empirical picture. This study aims to present a conceptual framework for the relationship between religious theology in Islam (Sunni WahhÄbi and Shia-ism) and the competitive conflict in the Gulf region, the struggle for dominance in the Middle East region, as a variable for the protracted conflict between Saudi Arabia and Iran, and to predict the future of relations between the two countries following the foreign policy of Muhammad bin Salman. A review of the discussion employing an inductive library research methodology. To generalize a deviation from purely accidental phenomena. In order to analyze this topic in greater depth, the author borrows theory from Max Weber regarding the protestant ethic and spirit of capitalism by placing religion as a belief system and state conflict as a structure of social group action. This study's findings assume that the issue of Sunni-Shia sectarianism is religious propaganda used to win the hegemonic competition in the struggle for territory and dominance in the Gulf region of the Middle East. Before the reign of Muhammad bin Salman, this condition had not changed substantially. In Weber's framework, there has been a distinction known as "ethical inter-minism" between two ethics. On the one hand, the structure of moral ethics is founded on the moral values of Sunni and Shia Islam. But on the political side, moral responsibility confronts the obligation to maintain the disintegration of the nation and state, which is a means to wage war.